Enhancing TPACK for Excellent Vocational Teachers: The Role of Teacher Engagement in Implementing the Merdeka Curriculum - ., Zaenab; ., Samsudi; Wahyudin , Agus; Hidayah, Isti (Journal of Ecohumanism, 2024)
Therefore, this paper aims to investigate the effect of teacher competency, school and teacher commitment on the effectiveness of the implementation of the Merdeka Curriculum. Employing a mixed methodologies design, this research investigates the impact of Teacher Pedagogical Competence (TPC), Technological Competence (TC), Content Competence (CC), School Infrastructure Support (SIS), and Teacher Professional Training (TPT) on curriculum encouraging. Moreover, the study examines mediation effects for Teacher Involvement in Learning Process (TILP) in the curriculum effectiveness relationship, as well as the moderating effects of Teacher Motivation (TM). The data is taken from 500 teachers randomly selected from five regions in Indonesia. The data were collected using a few online surveys, interviews and classroom observations. It shows that TPC and TC contribute significantly to the effectiveness of the Merdeka Curriculum with teacher involvement being the main mediator. Proper infrastructure and professional development also play considerable roles in ensuring effective implementation. These findings emphasize the need for continuous professional teacher development, technological integration, and infrastructure improvement to support the implementation of the Merdeka Curriculum. The findings offer helpful information for policymakers and educational leaders when optimizing curriculum delivery to enhance educational achievement in Indonesia.